Problematic smartphone use and sleep disturbance: the roles of metacognitions, desire thinking, and emotion regulation - Akbari, Mehdi; Seydavi, Mohammad; Sheikhi, Sonay; Spada, Marcantonio M. (Frontiers in Psychiatry, 2023)
Background: The association between problematic Smartphone use (PSU) and sleep disturbance is evidenced in the literature, but more research is required to investigate the potential factors that may influence the effect of PSU on sleep disturbance. Given the considerable prevalence of PSU (9.3 % to 36.7%) and sleep disturbance (55.2%) in Iran, the current study sought to examine an interactional model to test whether metacognitions about Smartphone use, desire thinking (verbal perseveration and imaginal prefiguration), and emotion regulation (expressive suppression and cognitive reappraisal) could have a moderating effect on the above-mentioned association. Method: This present study is a cross-sectional, observational study that was conducted between June and September 2022 in a convenience sample of Iranians (n = 603, Female = 419, Age = 24.61±8). Result: Despite the significant association between metacognitions about the Smartphone use, PSU, and sleep disturbance, metacognitions failed to predict sleep disturbance above PSU. A slope analysis showed, however, that a high (not low or moderate) levels of imaginal prefiguration strengthen the association between PSU and sleep disturbance, while a high (not low or moderate) level of cognitive reappraisal and expressive suppression dampen the PSU-sleep disturbance association. We also found that verbal perseveration and expressive suppression were unique predictors of sleep disturbance, while imaginal prefiguration and reappraisal only predicted sleep disturbance if they interacted with PSU. Conclusion: Theoretically, findings suggest that enhancing cognitive reappraisal (by 1 SD) and reducing imaginal prefiguration (by 1 SD), might protect against sleep disturbance by reducing its association with PSU. Limitations and future directions are discussed.